Five-year Survey of Bacterial Culture Isolates and Their Antibiogram in Pediatric Patients of Rural Tertiary Care Hospital of Central Gujarat - Krutika R Tandon; Prachi Vani; Rahul Tandon; Nirav Thakar; Swati Kamani; Amit Kumar (Pediatric Infectious Disease)
Aims and background: Most studies related to bacterial infections and their profiles in pediatric patients focus only on the pediatric intensive care unit (PICU) setup. Therefore, we undertook this study to review data on positive culture isolates in patients from all pediatric areas of our center, excluding the neonatal unit, for their profiles and antibiotic sensitivity patterns. Materials and methods: This was a retrospective study (5 years: 2017–2021) from hospital records including indoor patients (1 month to 18 years) from the PICU and pediatric ward. A total of 1,380 cultures (from any site) were sent, of which 706 were positive, excluding contaminations. Pertinent details were entered into Microsoft Excel and analyzed. Results: A total of 706 positive isolates were found in 468 patients, and the mean [interquartile range (IQR)] age was 63 (18, 144) months. Males were 65%. Among positive culture isolates, 30.9, 24.8, 17.3, 16.1, 1.6, and 8.9% were from blood, pus, urine, endotracheal tube/tracheostomy tube (ET/TT), cerebrospinal fluid (CSF), and others, respectively. The median (IQR) hospital stay was 10 (4, 22) days. Total deaths were 17 (3.6%). Among positive culture isolates, gram-negative organisms in 205 (43.8%), Staphylococcus aureus was found in 135 (28.8%), Salmonella typhi in 53 (11.3%), and Candida in 24 (5.1%) cultures. Gram-negative organisms showed variable sensitivity to β-lactam/β-lactamase inhibitors and carbapenems. Among S. aureus isolates, 74 (39%) were oxacillin-sensitive. Almost all Salmonella were sensitive to ceftriaxone. Conclusion: S. aureus was the single top isolate, with oxacillin resistance in almost two-thirds of isolates, whereas other gram-negative organisms were common nosocomial isolates with variable sensitivity to β-lactamase inhibitors and carbapenems. Clinical significance: It includes recent data on microorganism profiles and their antibiograms from the western part of India.